2020
DOI: 10.3389/fnut.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Ketogenic Metabolic Therapy as a Complementary or Alternative Approach for Managing Breast Cancer

Abstract: Breast cancer remains as a significant cause of morbidity and mortality in women. Ultrastructural and biochemical evidence from breast biopsy tissue and cancer cells shows mitochondrial abnormalities that are incompatible with energy production through oxidative phosphorylation (OxPhos). Consequently, breast cancer, like most cancers, will become more reliant on substrate level phosphorylation (fermentation) than on oxidative phosphorylation (OxPhos) for growth consistent with the mitochondrial metabolic theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 208 publications
0
30
0
Order By: Relevance
“…This analysis focused on the primary study outcome of body composition changes. Another potential benefit of a KD during radiotherapy that is mainly supported by preclinical data could be a synergistic anti-tumor effect mediated through the ketogenic state and its effect on a variety of molecular signaling pathways [47][48][49][50][51]. A randomized controlled trial conducted by Khodabakhshi and colleagues found an overall survival benefit (p = 0.046) for 25 locally advanced or metastatic breast cancer patients eating a KD during neoadjuvant chemotherapy compared to 18 control patients who received chemotherapy without dietary intervention [52].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis focused on the primary study outcome of body composition changes. Another potential benefit of a KD during radiotherapy that is mainly supported by preclinical data could be a synergistic anti-tumor effect mediated through the ketogenic state and its effect on a variety of molecular signaling pathways [47][48][49][50][51]. A randomized controlled trial conducted by Khodabakhshi and colleagues found an overall survival benefit (p = 0.046) for 25 locally advanced or metastatic breast cancer patients eating a KD during neoadjuvant chemotherapy compared to 18 control patients who received chemotherapy without dietary intervention [52].…”
Section: Discussionmentioning
confidence: 99%
“…ROS production is also greater in cancer cells than in normal cells (Chen et al, 2016 iScience Review 2015). The genomic instability and random somatic mutations seen in most cancers arise largely as downstream epiphenomenon of ROS production and OxPhos dysfunction (Fosslien, 2008;Bartesaghi et al, 2015;Galadari et al, 2017;Desler et al, 2010;Degtyareva et al, 2013;Seyfried et al, 2020). Furthermore, mitochondrial oxygen consumption increases, rather than decreases, during the S phase of the cell cycle in some cancer cells without generation of ATP further indicating that oxygen consumption was not connected to ATP synthesis through OxPhos (Olivotto et al, 1984).…”
Section: Is Oxygen Consumption Linked To Atp Synthesis Through Oxphosmentioning
confidence: 99%
“…Genomic instability and somatic mutations would arise as a consequence of protracted mitochondrial ROS production together with acidification of extracellular microenvironment (Seyfried et al, 2014). Metastasis arises from respiratory damage in cells of myeloid/macrophage origin that would use glutamine as a major fuel for ATP synthesis (Seyfried and Huysentruyt, 2013;Seyfried et al, 2020). The degree of tumor progression and malignancy can be linked directly to the energy transition from OxPhos to SLP.…”
Section: Is Oxygen Consumption Linked To Atp Synthesis Through Oxphosmentioning
confidence: 99%
See 1 more Smart Citation
“…The ketogenic diet is said to affect glucose metabolism [25] and gene expression [26,27] because of changes in the metabolic environment and ketone bodies acting as signal molecules [28]. The term "ketogenic metabolic therapy" has also been proposed from the ketogenic diet [29,30]. In the present study, blood glucose and insulin levels were significantly decreased, suggesting that the ketogenic diet directly affects the insulin/IGF-1 signaling pathway and PI3K activity.…”
Section: Discussionmentioning
confidence: 53%